Impact Accounting Strategic Management in Sustainable Construction Business Organizations, Thailand - Kasama Kasorn; Wilailak Wongchai; Phathamon Boonyarasai; Pheerapol Sriwichai; Pornchai Jedaman (SAGE Open)
Accounting strategic management to competitiveness and financial performance, including business operations of construction business organizations. This study aimed to investigate whether accounting strategic management remains a significant factor in sustainable construction business organizations through interviews with 30 Key informants, and the causal factors relationship to impact accounting strategic management in sustainable construction business organizations through a survey by questionnaire with 330 samples data in construction business organizations, Thailand. The findings of strategic accounting management on the factors include corporate and management accounting strategies, management accountants’ role, accounting information systems, and effective organizational performance, which are the impact of direct and indirect influences in sustainable construction business organizations. The effect of accounting strategic management on achieving business goals and objectives plays an important role in impacting the efficient financial operations of sustainable construction business organizations.